Using Songs to Reduce Language Anxiety in Speaking English (Classroom Action Research on Grade 8 Students of MTs Nurul Qodiri) - Mustafidah, Mustafidah; Suhono, Suhono; Hidayatullah, Rizky (Assyfa Journal of Multidisciplinary Education, 2025)
The purpose of this research was Descreasing Students' Language Anxiety In Speaking English Through Songs on Grade 8 Students of MTs Nurul Qodiri. This study used a class action research. This study was carried out in East Metro City's Metro District. Ten teenagers, ages 14 to 17, participated in this study. Additionally, the primary source of data for this study was interviews. The data findings in this study were analyzed using thematic analysis. The study's findings suggest that using Songs can reduce languange anxiety in speaking English at the eight grade of MTs Nurul Qodiri Lempuyang Bandar. It can be seen in the progress from pre-test to cycle 1 and cycle 2. The average score from pre-test 63 to post test 1 is 73, post test 2 is 81. In cycle I, 9 students passed the test. Moreover, in cycle 2 15 students got a score >75. It means that the result of cycle 2 had already achieved the indicator of success that was 83% of the students achieve the Minimum Mastery Criteria (MMC). Using Songs can improve the student’s learning activity in the eight grade of MTs Nurul Qodiri Lempuyang Bandar. It can be seen from the result of reflecting that the student’s activities on cycle pre-test were passive. Then, in cycle to cycle 2 the students become active, confident, and much better.